Analisis Implementasi Evaluasi Kinerja Pegawai di Kantor Camat Boronadu (Jurnal Riset Manajemen dan Akuntansi, 2025)
Human resources are a strategic asset that plays a crucial role in determining organizational success in achieving goals and facing increasing competition. Organizational performance is strongly influenced by employee competence and motivation, which are managed through human resource management, particularly performance appraisal. Performance appraisal aims to objectively, transparently, and continuously measure employee performance and serves as a basis for administrative decisions, career development, and performance improvement. However, in practice, performance appraisal often encounters various challenges, including the limited competence and commitment of appraisers as well as subjectivity influenced by personal relationships. These conditions result in performance evaluations that do not optimally contribute to employee capacity development and organizational productivity. Based on preliminary observations at the Boronadu Sub-District Office, several issues were identified, such as a lack of guidance from supervisors, limited understanding of employees regarding their main duties and functions, and ineffective communication between supervisors and employees, all of which negatively affect employee performance. This study aims to analyze the implementation of employee performance evaluation at the Boronadu Sub-District Office and to identify factors influencing its implementation. The findings of this study are expected to provide input for improving the performance evaluation system and enhancing employee performance in a sustainable manner.